THE INFLUENCE OF SOCIAL CAPITAL ON THE SUCCESS OF URBAN FARMING PROGRAMS AT THE DAHLIA FARMERS' GROUP SEMARANG CITY - Natama, Aliifa Jenica Athaya; Prayoga, Kadhung; Gayatri, Siwi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The concept of urban agriculture can overcome the problem of shrinking productive agricultural land. Urban agriculture can run successfully in communities that have good social capital. This study aimed to investigate the role of social capital in urban farming success within the Dahlia Farmer Group. Conducted from December to January 2024. This research uses the methods analysis technique used is quantitative and statistical in the form of multiple linear regression. This research shows that norms have an important role in supporting the success of urban agriculture by establishing SOPs for members. The contribution of norms is essential because they create the basis for effective coordination within the group and ensure the achievement of common goals. Trust and networks have proven to be less influential because urban farming relies more on management and knowledge than on interpersonal relationships. The differences in previous studies bring newness (gap) in the research to be conducted. This study will contribute new understanding of the relationship between social capital and urban agriculture in farmer groups in urban areas, namely the Dahlia Farmer Group. Suggestions for the Dahlia Farmers Group are to prioritize strengthening norms that support urban agriculture, such as strengthening digital networks, developing mentorship, organizing social activities, establishing partnerships with external parties, and implementing a reward system.